Résistances de l’huile d’olive dans la Tunisie coloniale - Mohamed Frini (L’Année du Maghreb)
Political submission in colonized Tunisia, during the end of the xixth and the beginning of the xxth centuries, found in olive oil a symbolic and yet thorough matter of resistance. Local producers as well as consumers purposefully resisted to imported oils, peanut and colza oils for instance, meant by the French administration to diversify not only production, commerce and revenue sources, but mainly to weaken old agricultural upper class. Hence, resistance became culinary, social and cultural, never economic however, as far as the attractive low price of the new imported oils is concerned.